Functioning of Deposits Guarantee Systems on the Example of Poland and Czech Republic - Florczak, Tomasz (Journal of Finance and Financial Law, 2015)
As a result of the many crises in the banking sectors, there was highlighted the need to ensure depositors disbursement of the funds. As a result, there was created the idea of deposit guarantee schemes. Currently, many countries include in its system of financial safety deposit guarantee institutions. Some of them play a significant role in maintaining the stability of the state of the banking sector through additional assistance to the affected banks. Other limited to the possible payout amounts warranty. The aim of the article is to present and evaluate different solutions for the deposit guarantee system. The research problem will be constituted to verify the assumption that the deposit insurance system in Poland works in the same way as the system in the Czech Republic – a country that has undergone a similar change of the political system.